Hubungan Aktivitas Merokok dan Laju Aliran Saliva pada Nelayan di Kelurahan Makawidey Kota Bitung - Supit, Aurelia S. R.; Kalebos, Miracle A. J.; Wahyuni, Rizka (e-GiGi, 2025)
Abstract: Smoking has become a public health issue with the prevalence of active smokers increasing every year. Saliva is the first biological fluid to come into direct contact with the harmful components of cigarettes. This exposure contributes to changes in the structure and function of saliva, including a decrease in its flow rate, which plays an important role in the development of oral and dental diseases. Fishermen are recorded as the group with the highest percentage of daily active smokers compared to other occupational groups. This was an analytical and observational study with a cross-sectional design. Sampling was done using purposive sampling technique, and data were analyzed using the chi-square test. The study measured the number of cigarettes consumed per day using a questionnaire and assessed the salivary flow rate. The results obtained a total of 102 subjects who met the criteria. The highest percentages were obtained in subject age of 46-55 years (47.1%), moderate smokers (42.2%), and low salivary flow rate category (61.8%). Bivariate analysis using the chi-square test showed a p-value of 0.023 (<0.05) indicating a significant relationship. In conclusion, there is a significant relationship between smoking activity and salivary flow rate among fishermen in Makawidey Subdistrict Bitung City. Keywords: smoking activity; salivary flow rate; fishermen Abstrak: Merokok menjadi persoalan kesehatan publik dengan prevalensi perokok aktif yang semakin meningkat setiap tahunnya. Saliva merupakan cairan biologis pertama yang berkontak langsung dengan komponen berbahaya dari rokok. Paparan ini berkontribusi terhadap perubahan struktur dan fungsi saliva, termasuk penurunan laju alirannya yang memegang peranan penting dalam perkembangan penyakit gigi dan mulut. Nelayan tercatat sebagai kelompok dengan persentase perokok aktif harian tertinggi dibandingkan kelompok pekerjaan lainnya. Penelitian ini menggunakan metode observasional analitik dengan desain potong lintang. Uji statistik menggunakan uji chi-square, dan pengambilan sampel menggunakan teknik purposive sampling. Penelitian ini dilakukan dengan menghitung jumlah rokok yang dikonsumsi dalam sehari menggunakan kuesioner dan pengukuran laju aliran saliva. Hasil penelitian mendapatkan sebanyak 102 subjek yang memenuhi kriteria penelitian ini. Persentase tertinggi didapatkan pada usia subjek 46-55 tahun (47,1%), kategori merokok sedang (42,2%), dan laju aliran saliva kategori rendah (61,8%). Hasil analisis bivariat menggunakan uji chi-square menunjukkan nilai p=0,023 (<0,05) yang menunjukkan hubungan bermakna. Simpulan penelitian ini ialah terdapat hubungan bermakna antara aktivitas merokok dan laju aliran saliva pada nelayan di Kelurahan Makawidey Kota Bitung. Kata kunci: aktivitas merokok; laju aliran saliva; nelayan